2018
DOI: 10.1007/s00411-018-0754-5
|View full text |Cite
|
Sign up to set email alerts
|

Gold-coated iron oxide nanoparticles trigger apoptosis in the process of thermo-radiotherapy of U87-MG human glioma cells

Abstract: Recently, gold-coated iron oxide nanoparticles (Au@IONPs) have received a great deal of attention in cancer therapy. In this in vitro study we aimed to investigate the anti-cancer effects of Au@IONPs core-shell nanoparticles when applied in thermo-radiotherapy. Moreover, we investigated the level of apoptosis induced in U87-MG human glioma cells after receiving a combinatorial treatment regimen (Au@IONPs + hyperthermia + radiotherapy). Firstly, the Au@IONPs nanocomplex was prepared and characterized. Cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The tumor growth curve in Figure 4 showed that the introduction of the AGuIX during the radiation process result in a markedly dose increasing effect compared to radiotherapy alone, thereby inhibiting the growth of solid tumors. Tumor cell apoptosis after radiotherapy is the basis of cell death (Garcia-Barros et al, 2003; Neshastehriz et al, 2018), and apoptosis imaging in vivo can achieve early detection of tumor post-radiation response, as well as accurate prediction of radiotherapy efficacy (Verheij, 2008). The 99m Tc-duramycin is a relatively mature apoptosis imaging agent and has been used in apoptotic imaging of various tumors (Johnson et al, 2013; Audi et al, 2015; Elvas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor growth curve in Figure 4 showed that the introduction of the AGuIX during the radiation process result in a markedly dose increasing effect compared to radiotherapy alone, thereby inhibiting the growth of solid tumors. Tumor cell apoptosis after radiotherapy is the basis of cell death (Garcia-Barros et al, 2003; Neshastehriz et al, 2018), and apoptosis imaging in vivo can achieve early detection of tumor post-radiation response, as well as accurate prediction of radiotherapy efficacy (Verheij, 2008). The 99m Tc-duramycin is a relatively mature apoptosis imaging agent and has been used in apoptotic imaging of various tumors (Johnson et al, 2013; Audi et al, 2015; Elvas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the procedures found in the literature, however, are based on non-aqueous SPION synthesis; e.g., thermal decomposition or micro-emulsion methods [ 24 , 28 , 29 , 30 , 31 , 32 ], which require potentially harmful substances or solvents in steps of their synthesis. For aqueous and non-harmful procedures [ 27 , 33 , 34 , 35 ], no studies were published, which shows the systematic optimization of the synthesis parameters and the evaluation of their effects on Au-SPION properties such as particle size, dispersion stability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Both iron and ROS are cautiously managed to maintain balance or to stabilize their functions, thus a potential kind of cancer therapy is focused on disrupting the redox homeostasis by introducing or eliminating iron in the cell. Iron overload presented as ferric ammonium citrate (FAC) or iron complexes, remarkably inhibits cell survival in various cancer types [5,163,164]. Previous studies have shown that FAC induces cytoplasmic vacuolation formation in an ATG5/ATG7-dependent manner, with elevated LC3-II (autophagic marker) [159].…”
Section: Iron Manipulating Strategies In Cancermentioning
confidence: 99%